A retrospective and cross-sectional study to evaluate potential drug - drug interaction in hospitalized pediatrics, Bandar Abbas, Iran - Motahareh Ahmadi; Abd Nazemi; Seyedeh Fatemeh Davoodpour; Fahimeh Gharaie Pour; Maryam Montaseri; Omid Safa (Shiraz University of Medical Sciences, 2018)
AbstractBackground: The incidence of drug interactions in hospitalized patients due to the administration of various drugs, the lack of proper monitoring and sometimes multiple patient's co-morbidities, is common. This study aims to evaluate potential drug-drug interactions (PDDIs) in pediatrics hospitalized in an educational pediatric hospital.  Methods: The present study is a retrospective cross-sectional study. The study population included patients hospitalized in different parts of Bandar Abbas pediatrics hospital. A total of 400 medical records were assessed. PDDIs were evaluated by Lexi-Comp drug interaction and SPSS software was used for data analysis.Result: Based on our results PDDIs were observed in 133 cases (33.25%). The mean ± SD of PDDIs per prescription was 1.97 ± 1.56.  The majority of the interaction were moderate (79.1%) with risk rating C (45.7%). Salbutamol, phenytoin, phenobarbital and clarithromycin were responsible for the most interactions with 95, 40, 25,17 of PDDIs, respectively.  Drug interactions with risk-rating X, observed in 5 cases. Number of drugs per prescription was significantly associated with PDDIs (P= 0.000)Conclusion: Although the prevalence rate of PDDIs in this study was lower than reported by recent studies, but careful evaluation of drug charts and implantation of educational programs for medical staff, should be considered.  Abbreviation PDDIs: Potential Drug-Drug InteractionsDDIs: Drug-Drug InteractionsED: Emergency departmentNICU: Neonatal Intensive Care UnitPICU: Pediatric Intensive Care Unit